Nucleus accumbens controls wakefulness by a subpopulation of neurons expressing dopamine D1 receptors - Luo, Yan-Jia; Li, Ya-Dong; Wang, Lu; Yang, Su-Rong; Yuan, Xiang-Shan; Wang, Juan; Cherasse, Yoan; Lazarus, Michael; Chen, Jiang-Fan; Qu, Wei-Min; Huang, Zhi-Li (Nature communications, 2018)
Nucleus accumbens (NAc) is involved in behaviors that depend on heightened wakefulness, but its impact on arousal remains unclear. Here, we demonstrate that NAc dopamine D 1 receptor (D 1 R)-expressing neurons are essential for behavioral arousal. Using in vivo fiber photometry in mice, we find arousal-dependent increases in population activity of NAc D 1 R neurons. Optogenetic activation of NAc D 1 R neurons induces immediate transitions from non-rapid eye movement sleep to wakefulness, and chemogenetic stimulation prolongs arousal, with decreased food intake. Patch-clamp, tracing, immunohistochemistry, and electron microscopy reveal that NAc D 1 R neurons project to the midbrain and lateral hypothalamus, and might disinhibit midbrain dopamine neurons and lateral hypothalamus orexin neurons. Photoactivation of terminals in the midbrain and lateral hypothalamus is sufficient to induce wakefulness. Silencing of NAc D 1 R neurons suppresses arousal, with increased nest-building behaviors. Collectively, our data indicate that NAc D 1 R neuron circuits are essential for the induction and maintenance of wakefulness. The nucleus accumbens regulates many behaviours that depend on arousal. Here the authors show that dopamine D 1 receptor neurons in the nucleus accumbens can directly regulate wakefulness.